Fish composition and diversity in Perak, Galas and Kelantan Rivers (Malaysia) after the major flood of 2014 - Amonodin, Mohamad Radhi; Hashim, Rohasliney; Hashim, Zarul Hazrin (Lucian Blaga University of Sibiu Publishing House, 2017)
Fish from three major rivers, namely the Kelantan River (KR) and the Galas River (GR) in Kelantan, and the Perak River (PR) in Perak, Malaysia, were caught using gill nets with different mesh sizes, cast nets, and the electroshock method. There were 14 fishes representing five families and five fish species were collected from the Kelantan systems in February 2015. While the Galas system holds more fish, 48 individual fishes comprising of four families and 10 fish species were found there. A total of 213 fish specimens representing 10 families and 22 species were captured in PR in May 2015. For diversity index, PR had the highest value due to the catchment area and the environmental condition: Shannon-Weiner index (H’) (2.54), Species Evenness (J’) (0.73) and Simpson’s Dominance (D’) (8.93), compared to GR (H’) (2.09) (J’) (0.603) (D’) (6.52) and KR (H’) (1.62) (J’) (0.47) (D’) (5.62).